2014
DOI: 10.3390/ijms15023025
|View full text |Cite
|
Sign up to set email alerts
|

Barley β-Glucans-Containing Food Enhances Probiotic Performances of Beneficial Bacteria

Abstract: Currently, the majority of prebiotics in the market are derived from non-digestible oligosaccharides. Very few studies have focused on non-digestible long chain complex polysaccharides in relation to their potential as novel prebiotics. Cereals β-glucans have been investigated for immune-modulating properties and beneficial effects on obesity, cardiovascular diseases, diabetes, and cholesterol levels. Moreover, β-glucans have been reported to be highly fermentable by the intestinal microbiota in the caecum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 50 publications
5
54
0
6
Order By: Relevance
“…The growth curves of L. acidophilus and L. delbrueckii were different in terms of both lag phase and number of colonies, a result mediated by their specific nutritional requirements and the ability of β‐polysaccharides like β‐glucan to cause the strain‐selective growth of microorganisms (Arena and others ).…”
Section: Resultsmentioning
confidence: 99%
“…The growth curves of L. acidophilus and L. delbrueckii were different in terms of both lag phase and number of colonies, a result mediated by their specific nutritional requirements and the ability of β‐polysaccharides like β‐glucan to cause the strain‐selective growth of microorganisms (Arena and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Prebiotics, primarily derived from non-digestible oligosaccharides, are non-digestible food substances that selectively stimulate the growth of favourable species of bacteria in the gut, benefitting the host. It is well reported that Oligo-fructose, fructo-oligosaccharide, inulin, and β-glucan have been used as prebiotics (Kaplan & Hutkins 2000;Smiricky-Tjardes et al 2003;Loh et al 2006;Arena et al 2014). It is well known that β-glucan acts as an immunostimulant to activate immune cells by binding to its specific receptor dectin-1, a c-type lectin receptor expressed on the surface of macrophages (Brown et al 2002;Vos et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Barley beta-glucan stimulated growth of Lactobacillus plantarum, L. acidophilus and L. fermentum in unstressed conditions and in in vitro conditions simulating digestion in the gut. Moreover, food matrices containing barley beta-glucans had positive effect on probiotic-enterocyte interaction (Arena et al, 2014). However, in another in vitro study, the authors did not observe support of growth of probiotic strains by oat and barley beta-glucans used as the sole carbon sources in fermentation media.…”
Section: Prebiotic Properties Of Cereal Beta-glucansmentioning
confidence: 88%